Metástasis sintomáticas en cerebro superiores a 8.5 cm3 manejados con radiocirugía - Lovo, Eduardo; Campos, Fidel; Caceros, Víctor; Minervini, Mario; Reyes, William (Revista Argentina de Neurocirugía, 2020)
Introduction: Current recommendations with regards to metastases larger than 2 cm specially in symptomatic patients suggest surgery as a first choice. We analyze the role of upfront radiosurgery as first line of treatment in such patients.Methods: 37 symptomatic patients that harbored tumors greater than 8.5 cc in volume were treated from 2011 to January 2018.Results: The median tumor volume was 12.5 cc (8.5-78.4), 9 (24%) patients were treated with LINAC with a volume of 20 cc (9.2-70 cc). The treatments with GammaRay were administrated to 28 (76%) patients, 9 (32%) of them with adaptive radiosurgery protocol, the prescription dose for the gamma group was 13.8 Gy (7.5-18Gy) mean dose of 17.9 Gy (13.2-23.3 Gy) with a mean volume of 16.3 cc (8.5-78.4 cc). Karnofsky score was 60 (50-70) the day of treatment and 80 (60-100) at 30 days (P=0.0001). At 30 days, 95% of the tumors had reduced in size in a 74% (11-95%) for those evaluated. Median survival was 19 months (4-34), with an accumulative risk of death from central nervous progression of 5.4%.Conclusions: Radiosurgery in our experience has shown to be effective in controlling large metastases, reducing the need for open surgery.
Keywords: Brain; Metastases; Breast Cancer; Radiosurgery; Neurosurgery; Gamma Knife; Linear Accelerators